Hamburger Hill - Carabatsos, Jim; Cheadle, Don; Dolan, Michael 1965-; James, Don; McDermott, Dylan; Nickles, Michael A. 1968-; Weber, Steven; O'Reilly, Harry; O'Shea, Daniel; Quill, Timothy Patrick; Swerdlow, Tommy; Vance, Courtney B; et al.
For ten days, the American soldiers of Bravo Company fight in Vietnam to take over Hill 937, also known as Hamburger Hill